BANGUNAN TAHAN GEMPA BERBASIS STANDAR NASIONAL INDONESIA - Suwandojo Siddiq (JURNAL STANDARDISASI, 2006)
When strong earthquake occurs, (Magnitude is larger than 6,0 SR), usually followed by earthquake damages, such as multi story buildings and non engineered structures (public houses), and big number of victims, in the area close to epicenter. If the location of hypocenter is under bottom of the sea, its depth is less than 30 km (shallow earthquake), the magnitude M is not less than 7.0, and the type of earthquake is thrust or dip-slip, the earthquake may be followed by tsunami (tsunami is Japanese words, means harbor sea-waves). Great tsunami with run up more than 2.0 meters is able to destroy every thing on the beach and kill big number of human lives.Earthquake shock will generate ground acceleration, and may cause building/housing damages and collapses. The damaged buildings are caused by weakness of building/house structures, such as: bad quality of building-materials, unperfected structural configuration, utilization of unsuitable building materials and/or building structures, and the last but most important is not implemented SNI-guidance regarding aseismic (anti-seismic) structures properly. This paper will discuss the weakness of public houses (Non Engineered Structures) and Multi story Structures (Engineered Structures), and the role or the function of SNI in improving quality and safety of buildings against earthquake motion.